The Role of Drug Metabolites in the Inhibition of Cytochrome P450 Enzymes - Mikov, M.; Ðanic, M.; Pavlovic, N.; Stanimirov, B.; Golocorbin-Kon, S.; Stankov, K.; Al-Salami, Hani (Springer France, 2017)
© 2017, Springer International Publishing Switzerland. Following the drug administration, patients are exposed not only to the parent drug itself, but also to the metabolites generated by drug-metabolizing enzymes. The role of drug metabolites in cytochrome P450 (CYP) inhibition and subsequent drug–drug interactions (DDIs) have recently become a topic of considerable interest and scientific debate. The list of metabolites that were found to significantly contribute to clinically relevant DDIs is constantly being expanded and reported in the literature. New strategies have been developed for better understanding how different metabolites of a drug candidate contribute to its pharmacokinetic properties and pharmacological as well as its toxicological effects. However, the testing of the role of metabolites in CYP inhibition is still not routinely performed during the process of drug development, although the evaluation of time-dependent CYP inhibition during the clinical candidate selection process may provide information on possible effects of metabolites in CYP inhibition. Due to large number of compounds to be tested in the early stages of drug discovery, the experimental approaches fo r assessment of CYP-mediated metabolic profiles are particularly resource demanding. Consequently, a large number of in silico or computational tools have been developed as useful complement to experimental approaches. In summary, circulating metabolites may be recognized as significant CYP inhibitors. Current data may suggest the need for an optimized effort to characterize the inhibitory potential of parent drugs metabolites on CYP, as well as the necessity to develop the advanced in vitro models that would allow a better quantitative predictive value of in vivo studies.